The Impact of Fibre Oxidation on the Preparation of Cellulose Nanocrystals (CNC) - Behzad Ahvazi; Christophe Danumah; Tri-Dung Ngo; Zhengxiang Zhu; Heather Lorenz (Biomass, 2022)
This study aimed to evaluate the effect of fibre oxidation on the extent of substituted sulfate on cellulose nanocrystals (CNC). In this investigation, fully bleached softwood (SW) and hardwood (HW) pulps from an Alberta pulp mill were oxidized under low (4%), medium (10%), and the higher-end of medium (14%) oxygen consistencies. The oxidized pulp samples were hydrolyzed with concentrated sulfuric acid under conventional procedures to produce CNC. The CNC materials were then characterized by different qualitative and quantitative techniques to evaluate the effect of oxidations on the number of substituted sulfates and the overall sulfate charge of isolated CNC to develop novel high-value applications. The experimental data show that fibre oxidation helped improve the overall CNC yield, with lower half-ester sulfate contents compared to the controls. The half-ester sulfate contents and the viscosity for SW CNC were found to be higher than their HW CNC counterparts. However, the thermal stability of CNC was found to be better for HW than SW pulps. The emerging data help to prepare and engineer CNC tailored to specific applications.